Analysis of students Interpretation of Quranic Values in Islamic Religious Education Learning at SMK Muhammadiyah 8 Medan - Rafindo Purba (Yayasan Rahmat Islamiyah, 2026)
This study aims to analyze students’ interpretations of Quranic values in Islamic Religious Education (IRE) learning at SMK Muhammadiyah 8 Medan. The focus of the research is on students’ understanding of Quranic values such as faith (aqidah), worship (ibadah), morals (akhlaq), and social interaction (muamalah), as well as how these values are internalized in their daily attitudes and behaviors. This research employs a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews with IRE teachers and students, and documentation. The findings reveal that most students are able to understand Quranic values conceptually; however, there are variations in the level of interpretation and practical application of these values in daily life. Factors influencing students’ interpretations include teaching methods, teacher role modeling, school environment, and family background. The study concludes that contextual Islamic Religious Education learning based on Quranic values plays a significant role in shaping students’ understanding and religious character.